1992
DOI: 10.1063/1.462170
|View full text |Cite
|
Sign up to set email alerts
|

Structural transitions in a monolayer of fluorinated amphiphile molecules

Abstract: We present results of an extensive x-ray diffraction study of a monolayer of C10F21CH2COOH spread on water (pH2) at 19.1 °C. Lever-rule analysis of the in-plane scattering is used to show that there is a coexistence region between ordered condensed islands and a dilute disordered phase. The coexistence region is found to be bounded by molecular areas of 29 Å2 and 2000±600 Å2, in agreement with the pressure-area isotherm. The molecular tilt of the ordered phase remains unchanged from closest packing (near colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
68
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 28 publications
15
68
0
1
Order By: Relevance
“…In addition, the limiting molecular area, that is, the cross-sectional area of a straight molecule is 0.482 (n = 3) and 0.402 nm 2 (n = 5) per molecule, which is much larger than the theoretical cross section of 0.296 nm 2 per molecule. [1,[18][19][20] In this manner, a short R f group has poor aggregation and apparent hydrophilic properties; these are supported by IR spectroscopy data discussed below.…”
supporting
confidence: 49%
“…In addition, the limiting molecular area, that is, the cross-sectional area of a straight molecule is 0.482 (n = 3) and 0.402 nm 2 (n = 5) per molecule, which is much larger than the theoretical cross section of 0.296 nm 2 per molecule. [1,[18][19][20] In this manner, a short R f group has poor aggregation and apparent hydrophilic properties; these are supported by IR spectroscopy data discussed below.…”
supporting
confidence: 49%
“…<80%, so that the monolayer surface pressure is very low) was shown to be a widespread phenomenon. This was demonstrated for a variety of amphiphiles, such as long fluorocarbon chain a-amino acids (Jacquemain et al, 1990) and carboxylic acids (Durra et al, 1987;Barton et al, 1988Barton et al, , 1992, hydrocarbon chain alcohols, amides, carboxylic acids and their cadmium or calcium salts (BiShm et al, 1994). Indeed the GID spectrum of the cadmium arachidate monolayer gave direct evidence of an ordered counterionic cadmium layer bound to the carboxylate head group.…”
Section: Crystalline Self-assembly Of Amphiphilic Monolayers On the Wmentioning
confidence: 99%
“…More extensive studies by Lundquist [13] and Peterson and colleagues [14][15][16][17] have revealed a complex polymorphism for monolayers of fatty acids and Peterson has produced a generic phase diagram in which the phase boundaries change systematically with acyl chain length. Structural studies by, for example, grazing incidence synchrotron X-ray diffraction, have revealed details of the molecular structures of some of these phases [17][18][19][20][21][22][23]. In Fig.…”
Section: Surface Pressure-molecular Area Isothermsmentioning
confidence: 99%